Diatoms to human uses: linking nitrogen deposition, aquatic eutrophication, and ecosystem services. Issue 7 (24th July 2017) - Rhodes, Charles; Bingham, Andrew; Heard, Andrea M.; Hewitt, Julie; Lynch, Jason; Waite, Randall; Bell, Michael D.
Abstract: Nitrogen (N) loading to aquatic ecosystems can lead to eutrophication, changing the ecosystem within a waterbody, including primary productivity, water clarity, and food web dynamics. Nutrient loading often first affects the primary productivity of aquatic systems through shifts in phytoplankton communities. However, ecologically important changes in phytoplankton are often not relatable to the general public—whose behavior would need to change to alter patterns of nutrient loading. Therefore, we use the STressor–Ecological Production function–final ecosystem Services Framework to develop 154 chains that link changes in biological indicators of aquatic eutrophication (a shift in phytoplankton community) to final ecosystem services that people use or appreciate. We identify 13 ecological production functions (EPF) within three different ecosystems (alpine lakes, lakes, and estuaries) that connect changes in phytoplankton and algae to ecological endpoints that the general public and policy makers can appreciate. Using the Final Ecosystem Goods and Services Classification System, we identify 18 classes of human beneficiaries that potentially will be impacted by a change in one of these endpoints. We further assign strength‐of‐science scores to each link within the EPFs for the 154 chains according to how well each link is supported by current peer‐reviewed literature. By identifying many pathways through which excess N loading in U.S. surface waters can affect ecosystems and ultimately the beneficiaries of ecosystem services, this work intends to draw attention to gaps in empirical ecological literature that constrain understanding of the magnitude of effects that excess N loading can have on human well‐being. Results highlight the importance of intersections between the natural and social sciences when managers and policy makers evaluate impacts from ecological stressors. A balance between knowledgeable specialists proved key to applying this approach and will continue to remain important.